2002
DOI: 10.1073/pnas.052703399
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of planning: A computational analysis using event-related fMRI

Abstract: To investigate the neural mechanisms of planning, we used a novel adaptation of the Tower of Hanoi (TOH) task and event-related functional MRI. Participants were trained in applying a specific strategy to an isomorph of the five-disk TOH task. After training, participants solved novel problems during event-related functional MRI. A computational cognitive model of the task was used to generate a reference time series representing the expected blood oxygen level-dependent response in brain areas involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
136
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(151 citation statements)
references
References 30 publications
(37 reference statements)
12
136
1
2
Order By: Relevance
“…The frontoparietal adaptive control network appears to include the dorsal attention network proposed by Corbetta et al (33). The dorsal attention network seems to be functionally connected to the IPL and dlPFC, regions previously implicated in control (9,34,35).…”
Section: Discussionmentioning
confidence: 88%
“…The frontoparietal adaptive control network appears to include the dorsal attention network proposed by Corbetta et al (33). The dorsal attention network seems to be functionally connected to the IPL and dlPFC, regions previously implicated in control (9,34,35).…”
Section: Discussionmentioning
confidence: 88%
“…Reasoning with neutral content resulted in greater activation in L/DLPFC cortex (over and above the neutral baseline) than reasoning with emotionally salient content (over and above the emotionally salient baseline). Consistent with this role, the L/DLPFC has been implicated in a series of "executive" cognitive tasks including the WCST (Drewe, 1974;Stuss et al, 2000), Tower of London (Fincham et al, 2002;Rowe et al, 2001;Shallice, 1988), the Stroop task (Perret, 1974;Weekes and Zaidel, 1996), design fluency (Jones-Gotman and Milner, 1977), cognitive estimation (Smith and Milner, 1984), planning and design (Goel and Grafman, 2000;, and tasks (like humor appreciation) requiring the "breaking of mental sets" (Goel and Dolan, 2001a;Shammi and Stuss, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…The finding suggested that these patients had deficits in inhibition control rather than planning. Nonetheless, the contribution of the PFC during the Tower of Hanoi has been verified by studies using functional Magnetic Resonance Imaging (fMRI) [7] and electroencephalogram (EEG) [8] [9]. Increased prefrontal-parietal intrahemispheric correlation was observed during the Tower of Hanoi task in both left and right hemispheres [9].…”
Section: Introductionmentioning
confidence: 95%